Air pollution associated with hospital visits for mental and behavioral disorders in Northeast China - Liu, Huo; Zhao, Hang; Huang, Jinling; He, Miao (Frontiers in Epidemiology, 2023)
Background Related studies have found that air pollution is an important factor affecting mental and behavioral disorders. Thus, we performed this time-series study to evaluate the relationship between short-term exposure to ambient air pollutants and visits to hospital by patients with mental and behavioral disorders in northeastern China. Methods We used quasi-Poisson regression models and generalized additive models to probe the links between air pollution and mental and behavioral disorders. The possible influences were also explored stratified by season, age and gender. Results We found that sulfur dioxide (SO2) had a cumulative effect on mental and behavioral disorders at lag04–lag07 and had the greatest effect at lag07 [Relative risk (RR) = 1.068, 95%CI = 1.021–1.117]. Particulate matter of size 2.5 μm (PM2.5) and SO2 had a cumulative effect on depression and both had the largest effect at lag07 (RR = 1.021, 95%CI = 1.002–1.041; RR = 1.103, 95%CI = 1.032–1.178); SO2 also had a cumulative effect on anxiety disorders, with the largest effect at lag06 (RR = 1.058, 95%CI = 1.009–1.110). In the stratified analysis, people are more susceptible in the cold season compared to the warm season and females and the 18–60-year age group are more sensitive to air pollutants. It is suggested to strengthen management and preventive measures to decrease air pollution exposure. Conclusion This study found an association between increased concentrations of air pollutants and increased outpatient visits for mental and behavioral disorders. We recommend that preventive and protective measures should be strengthened in an effort to reduce exposure to air pollution in order to maintain physical and mental health.